Amperometric cholesterol biosensor based on zinc oxide films on a silver nanowire–graphene oxide modified electrode. Issue 8 (8th February 2016) - Wu, Qiong; Hou, Yiting; Zhang, Mengdan; Hou, Xiaochun; Xu, Lin; Wang, Nana; Wang, Jianpu; Huang, Wei
Abstract : A highly sensitive and selective cholesterol biosensor is successfully fabricated in this work. Abstract : A highly sensitive and selective cholesterol biosensor is successfully fabricated in this work. Due to excellent conductivity and catalytic activity, silver nanowires (AgNWs) and zinc oxide (ZnO) are modified on an indium tin oxide (ITO) electrode with graphene oxide (GO) and chitosan (CS) to construct the novel amperometric biosensor. The composite of AgNW–ZnO successfully enhanced electron communication, and the electrochemical performances of the ChOx/ZnO/Ag/GO–CS/ITO electrode were investigated via scanning electron microscopy (SEM), cyclic voltammetry (CV) and impedance measurements. The linear response to cholesterol in the range of the fabricated biosensor is 0.25–400 mg dL −1 (6.5 μM to 10 mM) with a sensitivity of 9.2 μA μM −1 cm −2 . Moreover, the limit of detection (LOD) is 0.287 μM (S/N = 3), and the Michaelis–Menten constant is calculated to be about 0.295 μM in 0.1 M phosphate buffer solution (pH 7).